Kick plate position and track start biomechanics in elite swimmers - Cicenia, A.; Oster, C.; Mokha, M. (Journal of Exercise and Nutrition, 2019)
Introduction: Kick plate position in the track start is arbitrary, but may influence performance. The purpose of this study was to investigate the influence of standardizing kick plate positioning based on shin length. Methods: 15 elite swimmers participated in the study. Shin length was measured between the tibia`s lateral condyle and lateral malleolus. Participants were filmed with two 120Hz cameras while performing three starts at three kick plate positions (< shin length, shin length, and > shin length). We determined reaction time, block phase time, flight phase time, flight distance, underwater phase time, and time to the 15-m mark via Dartfish software. Data were reduced using repeated measures analysis of variance, p<.05 Results: Only reaction time (RT) was significantly different between the three kick plate positions (F(2,28)=4.713, p=.017). Post-hoc analysis showed RT was lower when kick plate distance was one shin`s length versus < shin length (0.173+0.034 vs 0.194+0.061 sec) and > shin length (0.173+0.034 vs 0.195+0.047 sec), p<.05. Finally, 9/15 (60%) participants produced faster 15-m times with the kick plate at shin` length. Conclusion: Coaches and athletes may consider using shin length as a guide for positioning the kick plate to enhance performance.